CURRENT STATE AND TRENDS OF MEDICAL TOURISM DEVELOPMENT IN LVIV REGION - PANKIV, N.; POKALCHUK, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Medical tourism is a new global trend that has resulted from globalization and is to travel to get medical care, improve their well-being and improve their health. This type of tourism is one of the main factors in the development of the country’s healthcare sector, replenishment of both state and local budgets, promotes foreign investment and creates a positive image of the country. According to the WHO, by 2022, tourism and health (jointly) will be one of the world's leading industries. And as the world's population ages, the development of medical and health tourism expects even more rapid growth.Ukraine is an attractive country for medical tourism: every year this type of tourist activity is developing more and more in different cities and regions. The Lviv region stands out, which is one of the most active in developing this type of tourism throughout the region. Given this, the research topic is relevant.The aim of the work is to identify current trends in the development of medical tourism as a promising, competitive and effective type of tourism in the Lviv region.The paper analyzes the current state and trends in the development of medical tourism in the Lviv region, outlines the main advantages of its development and identifies the problems that hinder it. Recommendations for the development of medical tourism in the Lviv region are given, in particular, the need to implement the infrastructure project "Medical Park", which will be located in Truskavets, Morshyn and Skhidnytsia. In addition, a new medical tour to the balneological resort of Lviv region - Skhidnytsia has been developed, the program of which provides accommodation and treatment in one of the best medical and health complexes of Skhidnytsia - "Kyivska Russ Resort Medical & Spa".In general, the implementation of the infrastructure project of the Medical Park will allow to unite Truskavets, Skhidnytsia and Morshyn into the main recreational center of Lviv region. And the developed medical tour will help to sign the tourist attractiveness of the resort and the Lviv region in general.
Keywords: medical tourism; Lviv region; Medical park; medical tour